A low-cost, multiplatform, open-source, and automatic system for lever-press timing tasks with rodents - Tércio Apolinário-Souza; Samuel Penna Wanner; Lucas Bicalho; Guilherme Menezes Lage (Journal of Open Hardware)
One of the main difficulties in the study of rodents comprises their training. In general, the training process is carried out under periodic and strict supervision by researchers, which can expose animals to stressful situations, and both increase the time and cost in the research development. With this in consideration, we propose a system using common electronic components that can be easily found and assembled with relative ease. The proposed system is multiplatform, allowing animals to be trained in their cages with the assistance of specific sensors. A conventional system of liquid reward was built using a plastic tube, end cap, pipe, water drinking bottle, micro switch, relay, reflectance sensor (infrared), Bluetooth module, LED, microcontroller, and a solenoid valve. Pressing the switch activates the system, releasing a specified amount of water which can be useful for laboratories seeking inexpensive, flexible, and easily constructed equipment.